2016
DOI: 10.1266/ggs.15-00051
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex MethyLight assay for the detection of DAPK1 and SOX1 methylation in epithelial ovarian cancer in a north Indian population

Abstract: Ovarian cancer is the fourth most common cancer in women worldwide. It is very heterogeneous at the clinical, histopathological and molecular levels and is caused by the accumulation of genetic and epigenetic changes in regulatory genes. More than 90% of ovarian cancers are epithelial in origin. Ovarian cancer is typically asymptomatic in its early stages, and, due to difficulties in early detection, most ovarian cancers are diagnosed at an advanced stage. The positive predictive value of CA-125, a routinely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Studies have also shown an inhibitory effect of SOX1 on a variety of tumors. In addition, many studies have shown that SOX1 can be used as a biomarker for a variety of tumors, such as cervical cancer, colon cancer, glioma, liver cancer, ovarian cancer, and small cell lung cancer [ 28 33 ]. However, to the best of our knowledge, the association between SOX1 and CCA has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown an inhibitory effect of SOX1 on a variety of tumors. In addition, many studies have shown that SOX1 can be used as a biomarker for a variety of tumors, such as cervical cancer, colon cancer, glioma, liver cancer, ovarian cancer, and small cell lung cancer [ 28 33 ]. However, to the best of our knowledge, the association between SOX1 and CCA has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…SOX1 is a member of the transcription factor sox family, which plays an important role in embryo and postnatal development. According to the current research, SOX1 also has a certain inhibitory effect on a variety of tumors, and many studies have proved that SOX1 can be used as a biomarker for a variety of tumors, such as cervical cancer, colon cancer, glioma, liver cancer, ovarian cancer, small cell lung cancer (24)(25)(26)(27)(28)(29), etc. But association between SOX1 and CCA has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have reported several biological mechanisms contribute to DAPK1's pro‐apoptotic character, especially in cases of cancer . For instance, DAPK1 affected the performance of the TNF‐α or IFN‐γ cascade in the ovarian cancer . Moreover, it has been demonstrated that inhibition of DAPK1 stimulates the apoptotic cell death and protects against ischemic neuronal damage that exhibited the potential effect of DAPK1 in ischemic injury .…”
Section: Discussionmentioning
confidence: 99%